Economic and monetary integration of the new Member States - helping to chart the route - Ignazio Angeloni; Michael Flad; Francesco Paolo Mongelli (European Central Bank (ECB), 2005)
This paper examines diverse aspects of the monetary integration of the ten new Member States (NMS) which joined the EU on 1 May 2004 into the euro area. Most NMS have undergone a rapid and deep transformation in all areas with considerable progress in their processes of reform and convergence, and more is underway. While trade integration with the other 15 EU Member States (EU15) has progressed quickly, convergence in output specialisation to EU standards has been slow, especially if measured in real terms. This may influence negatively the pace of real convergence. Most NMS lag significantly behind in building up and deepening their financial systems. There is also evidence that exchange rate flexibility may still be serving as a useful shock absorber for some NMS, and so far the evidence indicates that real exchange rates have moved, broadly speaking, in line with long term fundamental equilibria. On the positive side, many NMS are quite advanced relative to the euro area in the process of labour market and institutional reform (their labour market structures are more flexible than those of the euro area countries). There is also some evidence that a few NMS have a significant degree of business-cycle synchronisation with the euro area: hence, they may become less likely to be affected by different economic shocks. This, however, is not true for all NMS. The monetary policy institutions of the NMS have also converged to some degree - goals and institutional settings of central banks are now much more similar than before. A case-by-case approach to adopting the euro, based on country-specific conditions, seems natural due to the differences between the countries.
Keywords: E42; F13; F33; F42; 330; Optimum Currency Area; Economic and Monetary Integration; EMU.; Wirtschaftliche Konvergenz; Eurozone; Optimaler Währungsraum; EU-Mitgliedschaft; EU-Mitgliedschaft